Implementation of an IoT based home automation system using real time sensors - Mandal, Dipta; Hassan, Md. Sowad; Joydhar, Janet Santa (BRAC University, 2019)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.